Double Lateral Sliding Bridge Flap for the Treatment of Multiple Gingival Recessions: Case Series - Musalaiah, SVVS; Krishna, V Satya; Kumar, P Aravind; Nagasree, M (Journal of Orofacial Research, 2012)
Esthetic concerns of patient have become an essential part of dentistry, especially periodontics. Root coverage is being achieved by a variety of surgical techniques. The presence of shallow vestibule, inadequate width of attached gingiva and aberrant frenum pull may pose a challenge to cover the denuded root surface for which several independent surgical solutions are reported in the literature. This article highlights on two case reports in which a double lateral sliding bridge flap technique has been used for root coverage as a single step solution for the above mentioned mucogingival problems, if present simultaneously in any case.